Unlocking the Contradictory Outcomes of Presenteeism Through a Temporal Model: Effort Exertion as a Mediator - Chou, Chun-Yi; Mach, Merce (Frontiers in Psychology, 2021)
The effects of presenteeism, that is, working while ill or exhausted, are unclear, as previous research has yielded contradictory results. The aim of this study was thus two-fold: clarify the differential effects of short versus long-term presenteeism and corroborate the mediating effect of effort exertion on the relationship between presenteeism and work-related outcomes. We adopt a three-wave panel design and measure all the variables at three different points (initially, after one week and after one year) to understand the effects of presenteeism over time. Our sample consists of 361 Chinese employees working in diverse industries in Taiwan. We analyze the panel data using structural equation modeling and bootstrapping. Our results reveal that presenteeism is positively associated with increased effort, work engagement, and job performance after one week. By contrast, presenteeism is negatively associated with job performance and work engagement though positively associated with emotional exhaustion after one-year. Our research contributes to clarify paradoxical results regarding presenteeism’s consequences, as well as corroborating that effort exertion mediates the relationship between presenteeism and work outcomes. We also identify practical implications for organizations managing employees working remotely, a more common reality with the outbreak of the COVID-19 pandemic, the ensuing lockdowns and digitalization which has started to become the norm for a significant proportion of working sectors. Finally, we suggest recommendations for future research on presenteeism.